Bicuspid Aortic Valve: Genetic and Clinical Insights - Tessler, Idit; Albuisson, Juliette; Goudot, Guillaume; Carmi, Shai; Shpitzen, Shoshana; Messas, Emmanuel; Gilon, Dan; Durst, Ronen (AORTA, 2021)
Bicuspid aortic valve (BAV) is the most common valvular congenital heart disease, with a prevalence of 0.5 to 2% in the general population. Patients with BAV are at risk for developing cardiovascular complications, some of which are life-threatening. BAV has a wide spectrum of clinical presentations, ranging from silent malformation to severe and even fatal cardiac events. Despite the significant burden on both the patients and the health systems, data are limited regarding pathophysiology, risk factors, and genetics. Family studies indicate that BAV is highly heritable, with autosomal dominant inheritance, incomplete penetrance, variable expressivity, and male predominance. Owing to its complex genetic model, including high genetic heterogenicity, only a few genes were identified in association with BAV, while the majority of BAV genetics remains obscure. Here, we review the different forms of BAV and the current data regarding its genetics. Given the clear heritably of BAV with the potential high impact on clinical outcome, the clinical value and cost effectiveness of cascade screening are discussed.
Keywords: bicuspid aortic valve; genetics; congenital heart disease; thoracic aortic aneurysm; aortic dissection